Fleeting fields of Zadar (Croatia): characterizing millennial-scale urban landcover change, green space, and resilience into the twenty first century - Zaro, Gregory; Blaće, Ante; Baraka Perica, Josipa; Čelhar, Martina; Jurković Pešić, Filipa; Gusar, Karla (Frontiers in Ecology and Evolution, 2023)
Cities are a growing factor in global change today, but urbanization as a process has played a significant role in shaping our planet's environments for millennia. Exploring the longevity or persistence of cityscapes can therefore reveal qualities that may have strengthened urban sustainability or resilience over long periods. In the Mediterranean, many ancient cities lie in ruin and are fully formed archaeological sites, while others reflect continuous growth and expansion into the modern era, often replacing what has traditionally been a rural mosaic of green space with a more homogenized urban landcover. Green spaces like cultivated lands, urban forests, recreational parks, and green belts are essential components of urban resilience, as they build adaptive capacity by improving human health and livelihoods, reducing surface runoff and erosion, and mitigating urban heat island effects, among others. Protection of green space in urban and peri-urban contexts also offers greater capacity to transform in the face of uncertain change. This paper centers on the ancient city of Zadar along Croatia's Adriatic coast to characterize broad millennial-scale changes in urban landcover and green space. The results suggest that the distribution of urban landcover and green space appears to have been fairly stable for much of Zadar's 3,000-year history, which arguably played a significant role in its persistence into the present era. However, the pace and scale of urban development, as well as the corresponding losses of green space, have accelerated from the mid-twentieth century onward, depleting a major source of socioecological resilience that has benefitted the city since the Iron Age. Archaeological and historical fields of study provide a deep temporal context to these contemporary challenges and are well-suited to identify and promote the locally and historically distinctive character of surviving green spaces. Land use legacies stemming from Roman surveying and historic field clearance practices around Zadar have resulted in one of the most distinctive and well-preserved physical manifestations of ancient and historic land use in the Mediterranean. Recognition of their cultural significance, even in their diminished state, would add further value for their protection and continued capacity toward urban resilience in the next century.